THE INFUSION OF CRITICAL THINKING SKILLS INDICATORS AND MICROLEARNING PRINCIPLES IN THE ENGLISH READING Materials for Vocational School Students: A Content Analysis - Sumarni, Sri; Salsabila, Farah (University of Kuningan, 2023)
This study aims to reveal the critical thinking skills indicators and microlearning features integrated in the English reading materials for vocational school students in Indonesia. A content analysis was employed to examine reading materials available in the English Coursebook Work in Progress for SMA/SMK/MA Grade X published by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia 2022. The critical thinking skills analysis was meant to capture to what extend do the reading materials coverage signify to the lifelong learning, while the microlearning features investigation was meant to portray how the reading materials are presented to support self-directed learning. 8 critical thinking skills indicators proposed by Anderson and Krathwohl. (2001) were hired as the parameters in determining the integration of the critical thinking skills. Microlearning framework proposed by Allela (2021) were used to determine the reading lesson sequences, with which instructional methods associating each sequence. The results revealed that the reading materials for grade X are presented in 8 printed texts covered descriptive, recount, procedures, expository and narrative. These texts have potentially carried critical thinking skills indicators. The contexts are all pictures and instructions that have potentially presented 3 critical thinking skill indicators. The activities cover 15 comprehension activities and 4 beyond the comprehension activities; 7 Critical thinking indicators are potentially embedded in this part. The reading materials presentation, one set are clearly sequenced in the framework of microlearning covers pre-text, text, and post-text. While the other 7 sets sequenced text and post-text. The analysis indicated most of the critical thinking indicators integrated in the reading materials are under analysis and evaluation.